Out of ERmita ; Sunken San Diego Making it [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Manila Mayor Alfredo Lim's drive to eradiate prostitution. The galleon ship San Diego was discovered in the waters of Batangas with its reasures still intact. Mon David making it to the music industry.
Out of Ermita (17 min.) -- Sunken San Diego (14 min.) -- Making it (15 min.)
VHS
Keywords: San Diego Fortune Inland Ship; Social problems; Inland water transportation -- Philippines; Prostitution -- Philippines -- Ermita (Manila).; Tourist trade -- Philippines; Manila -- Nightclubs, dance halls, etc